2013
DOI: 10.1007/s12020-013-9968-0
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of thyroid nodules and its relationship with metabolic parameters in a Chinese community-based population aged over 40 years

Abstract: To investigate the prevalence of thyroid nodules (TN) among a community population aged >40 years and to explore the association between TN and its metabolic risk factors. Data from 9,533 adults aged over 40 years who participated in the epidemiological investigation of thyroid nodules in a Chinese community-based population from June to December 2011 were included in the analyses. We compared the levels of metabolic indices between the TN group and healthy controls. The prevalence of TN was 46.6% (39.7%, men;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
51
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 59 publications
(61 citation statements)
references
References 25 publications
5
51
2
3
Order By: Relevance
“…Thyroid cancer has become the most common form of cancer among Chinese women aged below 30 years old6. Our previous study has showed that by using ultrasound the prevalence of thyroid nodule was 46.6% in population aged above 40 years old8. However, only 7–15% of them are supposed to be cancerous according to the recent guideline from American Thyroid Association (ATA)5.…”
mentioning
confidence: 99%
“…Thyroid cancer has become the most common form of cancer among Chinese women aged below 30 years old6. Our previous study has showed that by using ultrasound the prevalence of thyroid nodule was 46.6% in population aged above 40 years old8. However, only 7–15% of them are supposed to be cancerous according to the recent guideline from American Thyroid Association (ATA)5.…”
mentioning
confidence: 99%
“…In addition to gender, other age-related conditions including hypertension, diabetes, and underweight were found to independently correlate to TNs. The associations between TNs and hypertension as well as diabetes have been reported in general population [8,23,24]. Previous studies have investigated the relationship between obesity and TNs, indicating that people who were overweight and with a higher BMI were more likely to have TNs than those who were not [5,21,25].…”
Section: Discussionmentioning
confidence: 82%
“…In replace, more chances will be given to patients who truly need thyroidectomy for higher risk of malignancy. Given the high prevalence of thyroid nodule in our community (Guo et al, 2013) and limited healthcare resources, it is worthwhile to reconsider the algorithm when referring a patient for thyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of thyroid nodule is about 18-40% in adult Chinese Guo et al, 2013;Liu et al, 2013). However, only 5-10 percent of all thyroid nodules are malignant.…”
Section: Introductionmentioning
confidence: 99%